A Production systems study on Econotrade, Inc. - Cancio, John Michael (College of Engineering, 2003)
Econotrade Inc. is a manufacturer of Metal House wares and Furnishings. They manufacture various kinds of organizer racks and ppliance base rolers, the ADAPMO and REFMO being the more famous ones. They boast of export qiality products that are catered to a wide range of market segments, they cater their [rpducts to different appliance stores and large chain of malls nationwide, the like of Shoemart, Inc., Ever Emporium, and Pilipinas Makro. Econotrade maintains its work-force to produce efficiently and effectively for the company. Econotrade maintains its work-roce at a level where it can benefit the most because of its relatively young and highly skilled crew. THere were three major problems identified with respect to the Production system of Econotrade: first, an inaccurate forecasting technique was employed. Most problems are caused by inaccurate forecasting namely, aggregate planning schedules disruptions and incorrect inventory levels and poor production scheduling, which is a major problem to be addressed. Second, as mentioned there is poor production scheduling and this affects the delivery and service of the company. Third, Facility Layout problems exists within the company's plant and it affects working spaces among operators and as well as storage space of RM, WIP and FG. The appropriate forecasting technique recommended by the group is the seasonal factor method, this gives a very low Mean Absolute Deviation of 66.06 for Product group 1, and 107.6 for Product group 2 compared to a Moving Average with n=3 & 6. For the Aggregate Planning problem, Product Families are formed for easier aggregation of products for scheduling. The Transportation method for linear programming was used to solve the current production scheduling problems; a production schedule for the year 2003 was computed for the company with the corresponding production costs. The Facility Layout recommendation considers elimination of disrputed work flors and providing for more directed work flows. Total load-distance score is lower with 10075 compared to the current layout which is 24070. Machine placement needs to be reconfigured and storage areas are decongested in the proposed layout. On top of these three major Production and Operation management problems the group addressed also the Inventory Management concern of the company. There are three classes of items based on dollar-usage: A, B, & C. Continuous Review System is applied to Class A items while a two-bin visual may be implemented for Classes B & C items.